2010
DOI: 10.1111/j.1365-2435.2010.01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional explanations for variation in bark thickness in tropical rain forest trees

Abstract: Summary1. The complex structure of tree bark reflects its many functions, which include structural support as well as defence against fire, pests and pathogens. Thick bark, however, might limit respiration by the living tissues of the trunk. Nevertheless, little research has addressed community-level variation in bark thickness, and to the best of our knowledge, no one has tested multiple hypotheses to explain variation in bark thickness. 2. We conducted an extensive survey of bark thickness within and among s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(158 citation statements)
references
References 39 publications
7
146
1
4
Order By: Relevance
“…The long time of experiments indicates the complexity of the processes of filling the bark retention container. Paine et al (2010) showed that total bark thickness is dependent on rhytidome thickness. Given the strong dependence of bark thickness H on the breast height diameter of trees for particular species (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The long time of experiments indicates the complexity of the processes of filling the bark retention container. Paine et al (2010) showed that total bark thickness is dependent on rhytidome thickness. Given the strong dependence of bark thickness H on the breast height diameter of trees for particular species (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A longer dry season thus simultaneously filters for wood traits related to resource conservation, and conversely for leaf traits related to resource acquisition (Table S4), suggesting that tropical trees can invest differentially in wood and leaf tissues to optimize their performance across environmental gradients. The functional significance of bark thickness in tropical forests is still unclear (Paine et al 2010), but our results suggest that bark thickness could be related to climatic parameters. Additionally, changes in leaf area could also be affected by climate, because smaller leaves could better avoid overheating by limiting the surface irradiated by the sun.…”
Section: P R E D I C T I N G C O M M U N I T Y F U N C T I O N a L Cmentioning
confidence: 95%
“…Cerrado apresentam características que lhes conferem resistência ou que favorecem sua rápida recuperação quando há ocorrência de fogo (COUTINHO, 1990;PAINE et al, 2010;SATO et al, 2010). Entre estas características podemos destacar ritidomas espessos e corticosos (HOFFMANN et al, 2009), órgãos de reserva subterrâneos MIRANDA et al, 2002) e elevado investimento em biomassa de raiz (HOFFMANN; FRANCO, 2003a;OLIVEIRA et al, 2005).…”
Section: Algumas Investigações Indicam Que Grande Parte Das Espéciesunclassified
“…presença de ritidomas espessos e corticosos HOFFMANN et al, 2009;MIRANDA et al, 2002;PAINE et al, 2010;PAUSAS, 2014), presença de órgãos de reserva subterrâneos (CLARKE et al, 2013;MIRANDA et al, 2002), nível de investimento em biomassa de raiz (HOFFMANN; FRANCO, 2003a;OLIVEIRA et al, 2005) e capacidade de rebrota (CLARKE et al, 2010;HOFFMANN;MOREIRA et al, 2008;RIBEIRO et al, 2012).…”
Section: Introductionunclassified
See 1 more Smart Citation